2006
DOI: 10.1128/ec.00039-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Fusarium fujikuroi TOR Kinase in Nitrogen Regulation and Secondary Metabolism

Abstract: In Fusarium fujikuroi, the biosynthesis of gibberellins (GAs) and bikaverin is under control of AreA-mediated nitrogen metabolite repression. Thus far, the signaling components acting upstream of AreA and regulating its nuclear translocation are unknown. In Saccharomyces cerevisiae, the target of rapamycin (TOR) proteins, Tor1p and Tor2p, are key players of nutrient-mediated signal transduction to control cell growth. In filamentous fungi, probably only one TOR kinase-encoding gene exists. However, nothing is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 70 publications
7
81
2
1
Order By: Relevance
“…Here, we showed that rapamycin treatment increases transcript levels of genes involved in nitrogen catabolism, such as Nit1, supporting a role of TOR in nitrogen catabolite repression of F. oxysporum. This result is in agreement with a previous study showing that rapamycin activates expression of nitrogen metabolismrelated genes, such as ammonium permease and uricase in F. fujikuroi (Teichert et al, 2006).…”
Section: Role Of Tor and Meab In Nitrogen Repressionsupporting
confidence: 94%
See 3 more Smart Citations
“…Here, we showed that rapamycin treatment increases transcript levels of genes involved in nitrogen catabolism, such as Nit1, supporting a role of TOR in nitrogen catabolite repression of F. oxysporum. This result is in agreement with a previous study showing that rapamycin activates expression of nitrogen metabolismrelated genes, such as ammonium permease and uricase in F. fujikuroi (Teichert et al, 2006).…”
Section: Role Of Tor and Meab In Nitrogen Repressionsupporting
confidence: 94%
“…Similarly, in F. fujikuroi, rapamycin was shown to activate AreA-regulated genes in the wild type but not in the DareA background (Teichert et al, 2006). Moreover, a gln3 gat1 double mutant of S. cerevisiae was blocked in rapamycin-mediated induction of the nitrogen-regulated genes MEP2 and GLN1 and was weakly resistant against rapamycin (Beck and Hall, 1999).…”
Section: Dual Role For Area As Activator Of Nitrogen Catabolic Genes mentioning
confidence: 96%
See 2 more Smart Citations
“…A number of other protein kinases have been implicated in transduction of the environmental signals including the TOR kinase and MAP kinases. The TOR kinase, characterized in yeast as responsible for regulating nutrient mediated growth signaling, has recently been implicated in the biosynthesis of a fungal secondary metabolite (Teichert et al, 2006). Nutrient regulation of AF and ST biosynthesis may be mediated by cAMP levels.…”
Section: G Protein Signaling and Protein Kinasesmentioning
confidence: 99%